Fun with mathematic and origami: water lily origami / Masnira Ramli ... [et al.] - Ramli, Masnira; Wan Nordin, Wan Nurul Husna; Sa’at, Amirah; Lakasa, Nurul Fazila (2021)
Ethnomathematics is related between culture and mathematics. Generally, culture affect mathematics, as does mathematics affect culture. In this paper, to show the relations between culture and mathematics, the origami of water lily model and the basic concept of geometric such as symmetrical line and angle is discussed. Origami is an art originally from Japan that represent an interesting geometric construction due to their simplicity and technique by using properties of origami. For origami making methods, the basic folding method needs to be known. Manually, design of origami begins with a square paper, but by using different version, origami’s properties and basic making of origami will be discussed graphically. To shape the base of water lily origami, the maker needs to satisfy all the properties to show that the origami model can be constructed just like constructing using straightedge and compass. The aim of this study is to create a base for water lily origami by using Treemaker and Reference Finder software. At the same time, symmetrical line and angle of origami must be ensured exactly so that the model formed is balance and real. Generally, for this model of origami, two properties of origami have been determined that is involving four basic symmetrical line and two basic angle that is 45o and 90o. Clearly mathematical knowledge is extensive, there are no limits.